Contribution of the STAT4 rs7574865 gene polymorphism to the susceptibility to autoimmune thyroiditis in healthy Turk population and psoriatic subgroups - Hiz, Meliha M. (Cent Eur J Immunol, 2016)
INTRODUCTION: STAT4 is an important transcription factor that activates gene transcription as a response to cytokines. Recently, the influence of STAT4 gene on autoimmune disease has been widely studied in many different immune-related diseases. Autoimmune, metabolic and cardiovascular disorders are more common in psoriatic patients. STAT4 may be a unique gene that switches on in autoimmune-related thyroid disease in psoriatic patients. The aim of the study: To explore the association of a STAT4 rs7574865 polymorphism to autoimmune thyroid diseases in the general Turkish population and psoriatic subgroups. MATERIAL AND METHODS: A total of 132 psoriatic patients and 118 non-psoriatic volunteers were genotyped for STAT4 rs7574865 using real time PCR. Twenty-four of the psoriatic patients and 15 of the non-psoriatic volunteers have autoimmune-related thyroid diseases. RESULTS: The prevalence of the T allele [OR = 4.37; 95% CI: 1.05-19; p = 0.03] of the STAT4 rs7574865 was higher in individuals with autoimmune-related thyroid diseases among the all non-psoriatic volunteers. The volunteers with autoimmune-related thyroid diseases has an increased allele positivity and carriers having at least one of the risk allele was significantly higher than in counterparts with a GG wild genotype [ORGT/TT vs. GG: 1.73; 95% CI: 0.09-32; p = 0.03]. Yet, there was no evidence of an association between rs7574865 and autoimmune-related thyroid disease in psoriatic patients. CONCLUSIONS: The STAT4 rs7574865 polymorphism increases autoimmune-related thyroid disease susceptibility among the general population but not in psoriatic patients.